Progress in dilithium initiators for anionic polymerization - JING Meng-na1,2, DONG Jing2, ZHANG Ding-jun1 (Hecheng xiangjiao gongye, 2023)
"The different types, synthesis methods and characteristics of dihalogenated alkanes, naphthalenes, diolefins and their oligomers, as well as other new types of dilithium initiators for anionic polymerization were summarized with 34 references. "